(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Central venous catheterization (CVC) is an essential procedure in surgical practice, providing reliable venous access for hemodynamic monitoring, fluid resuscitation, administration of vasoactive medications, total parenteral nutrition, and renal replacement therapy. Despite its clinical importance, CVC insertion is associated with mechanical, infectious, and thrombotic complications that may adversely affect patient outcomes. Objectives: To evaluate the indications for central venous catheterization and determine the incidence and pattern of early and late catheter-related complications among surgical patients in a tertiary care teaching hospital. Methodology: This descriptive cross-sectional observational study was conducted in the Department of General Surgery, Calcutta National Medical College & Hospital, Kolkata, over one year (June 2023–May 2024). A total of 172 consecutive surgical patients aged more than 12 years who required central venous catheterization were included. Demographic characteristics, indications for catheterization, insertion site, catheter duration, and procedure-related complications were recorded prospectively. Data were analyzed using SPSS version 27.0, and statistical significance was considered at p<0.05. Results: The mean age of the study population was 54.4±15.67 years, with most patients belonging to the 51–60-year age group. Difficult peripheral venous access was the commonest indication for CVC placement (51.2%), followed by parenteral nutrition (23.3%). The subclavian vein was the preferred insertion site (45.9%). Arterial puncture was the most frequent early complication, whereas catheter occlusion was the most common late complication. Overall, the incidence of both early and late catheter-related complications was low. A significant association was observed between age and the indication for catheterization (p=0.025), while no significant association was found with sex (p=0.184). Conclusion: Central venous catheterization is a safe and effective procedure in surgical patients when performed using meticulous aseptic technique and standardized protocols. Appropriate insertion-site selection, adherence to evidence-based catheter care practices, and early recognition of complications can further enhance procedural safety and improve patient outcomes.